Investigation of electrical, corporeal, ocular, and aquaphobic properties of zirconia thin-films by varying substrate temperature for high voltage insulators - Sujit Kumar; Sasanka Sekhor Sharma; Jayant Giri; Vikramaditya Dave; Mohammad Amir; Hitesh Panchal (Journal of Asian Ceramic Societies, 2024)
ABSTRACTThe addition of ZrO2 nanoparticles to porcelain insulators and its influence on their electrical and corporeal characteristics are studied throughout a wide range of sintering temperatures. The DC magnetron sputtering with a 99.99% pure zirconium target is utilized to create zirconium oxide thin films on glass and silicon substrates in a 12-inch-diameter chamber. Different temperatures were used to sinter the produced samples (room temperature (RT) − 400°C) for 1 h with gas pressure of 15 mTorr for all depositions. Scanning electron microscopy (SEM) was used to characterize the microstructures of a subset of the samples. In order to assess the physical and microphysical changes brought on by an increase in substrate temperature, the phase composition of various nanocomposites samples was determined using X-ray diffraction (XRD). The breakdown strength, electrical resistivity, and dielectric constant were measured to assess the electrical attributes of the various samples. The obtained findings showed that the electrical and corporeal characteristics of samples sintered at RT were the best. In addition, the sample of nanocomposite porcelain sintered at room temperature has excellent insulating qualities, confirming the possibility of electro-technical porcelain manufacture (water contact angle = 103.5º), dielectric constant = 24.4, refractive index = 2.15, and bandgap = 5.33.